PENGARUH TINGKAT SUKU BUNGA TERHADAP PENYALURAN KREDIT KONSUMTIF PADA PT. BANK RAKYAT INDONESIA Tbk CABANG SUNGGUMINASA - Badaruddin Badaruddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This type of study is explanatory research (explanation), where these studies can be evaluated in accordance with the level of depending objects. In theexplanatory level this research includes the study of descriptive, which research conducted to determine the value of independent variable, either one or more variables (independent) without making comparisons, or connect between variables one with other. This research is using secondary and primary data. Secondary data in this study was obtained from the company documents in the form of written reports that are generated periodically, while the primary data obtained based on observations and interviews with leadership and employees.Testing hypotheses using simple linear regression analysis. The results of this study indicate that interest rates have a positive impact on consumer credit distribution in PT. Bank Rakyat Indonesia Tbk, Branch Sungguminasa.Based on the results of data analysis and hypothesis testing with the coefficient of determination (r2), amounting to 1.1025 or 11,025% interest rate changes affect the amount of the consumer credit distribution while the remaining 88,975% is influenced by other indicators that are not included in this study. To the authors suggest that the banks can maintain the stability of interest rates on loans.